Effects of prehospital hypothermia on transfusion requirements and outcomes: a retrospective observatory trial. Issue 3 (30th March 2016) - Klauke, Nora; Gräff, Ingo; Fleischer, Andreas; Boehm, Olaf; Guttenthaler, Vera; Baumgarten, Georg; Meybohm, Patrick; Wittmann, Maria
Abstract : Objectives: Prehospital hypothermia is defined as a core temperature <36.0°C and has been shown to be an independent risk factor for early death in patients with trauma. In a retrospective study, a possible correlation between the body temperature at the time of admission to the emergency room and subsequent in-hospital transfusion requirements and the in-hospital mortality rate was explored. Setting: This is a retrospective single-centre study at a primary care hospital in Germany. Participants: 15 895 patients were included in this study. Patients were classified by admission temperature and transfusion rate. Excluded were ambulant patients and patients with missing data. Primary and secondary outcome measures: The primary outcome values were length of stay (LOS) in days, in-hospital mortality, the transferred amount of packed red blood cells (PRBCs), and admission to an intensive care unit. Secondary influencing variables were the patient's age and the Glasgow Coma Scale. Results: In 22.85% of the patients, hypothermia was documented. Hypothermic patients died earlier in the course of their hospital stay than non-hypothermic patients (p<0.001). The administration of 1–3 PRBC increased the LOS significantly (p<0.001) and transfused patients had an increased risk of death (p<0.001). Prehospital hypothermia could be an independent risk factor for mortality (adjusted OR 8.521; p=0.001) and increases the relative risk for transfusion by factor 2.0 (OR 2.007; p=0.002). Conclusions: Low body temperature at hospital admission is associated with a higher risk of transfusion and death. Hence, a greater awareness of prehospital temperature management should be established.